The Role of Product Innovation and Local Culture in Strengthening Marketing Strategy and Driving Economic Growth of MSMEs - Sonani, Nia; Islami, Vina; Sukayat, Harmoko; Nadzri, Suhaila binti; Rusdian, Suca (Universitas Brawijaya, Indonesia, 2025)
Product innovation and the utilisation of local culture are significant in strengthening marketing strategies and encouraging the economic growth of MSMEs. This study aims to analyse the role of local culture-based product innovation and marketing strategies in improving the economic development of MSMEs in West Java Province. This study uses a quantitative approach with a correlational design. The population involved was MSME players in West Java, with a purposive sampling technique and a sample size of 200 respondents. Data were collected through questionnaires and structured interviews. The results showed that local culture-based product innovation has a significant positive influence on marketing strategies, thus contributing to the economic growth of MSMEs. This study emphasizes the importance of incorporating local culture into marketing strategies to enhance product attractiveness and the competitive position of MSMEs in the market. The study suggests that MSMEs should continue to develop locally culture-based product innovations and enhance their marketing strategies to maximize contributions to local economic growth, especially in the face of global challenges.